Food security and Sustainable Forest Management (SFM) implementation at the Forest Management Unit (FMU) level: A case study in Salarom Taka, Nabawan, Sabah - V Atin; A L Ibrahim; Walter Lintangah (2022)
The forest managed under Sustainable Forest Management (SFM) could contribute to food security, especially for vulnerable communities living in the forest's vicinity. This study was conducted to determine the local community's perception of the SFM implementation and food security in Salarom Taka, Nabawan. The interrelation between forest and community's food security was assessed based on the availability and utilisation of various food resources from four accessible areas: natural forest reserve, forest plantation, alienated land, and resources purchased from the market. The food resources are mainly available and accessible through purchasing, followed by alienated land, forest reserve and forest plantation. Forest contributions are significant, with most communities utilising forest resources for direct food consumption and using fuelwood for food processing. The community depends on the forest to intensify their agricultural production to sustain their food security. The community are less aware of the SFM implementation in their area, but agree with better access to clean water sources, health and education facilities, and more employment opportunities. The roles of forests are strengthened through SFM policy which ensures the forest is managed sustainably, enhancing economic and environmental values that could benefit current and future generations.